The Customer Relationship Management (CRM) Assessment Of Heitech Padu Berhad - Zaharuddin, Mohd Dzulkaedah (2004)
HeiTech's specialists and consultants have worked with and delivered comprehensive and cutting edge and-to-end solutions to the Malaysian market for over 15 years. As a result of the evolving customer centric business core, Heitech now faces an opportunity to bridge their customer relationship with the espertise provided. The successful of the Customer Relationship Management (CRM) strategies will determine HeiTech's readiness in responding to the customer needs and sustaining the customer's loyalty.